Impact of Nuts Consumption On Antioxidant Status and Pro-Oxidant Parameters in Healthy Human Volunteers - Al-Habib, Omar A.M.; AL-Kass, Suad Y.; Jasim, Kajeen H. (Science Journal of University of Zakho, 2016)
The aim of the current research was to study the effect of consumption of a mixture of almond and pistachio on antioxidants and pro-oxidants levels in healthy human volunteers. This dietary intervention study was carried out during the period from February to March, 2013 on a total of 48 apparently healthy males students from Military Academy / Zakho, Kurdistan Region- Iraq. Blood samples were withdrawn from all volunteer who were living in a controlled environment and analyzed for the determination of serum antioxidants, pro-oxidants. Parameters were obtained at baseline, 3 and 6 weeks after daily consumption of 50 gm. of a mixture of almond and pistachio. The results of the current study demonstrated that daily consumption of 50 g of almond and pistachio mixture for 3-6 weeks, significantly increased (P<0.05-0.005) the levels of total antioxidant, Ceruloplasmin, Superoxide dismutase and Glutathione reductase. On the other hand, the levels of the pro-oxidants Malonaldehyde and Peroxy- nitrite were significantly decreased (P<0.005) after 6 weeks of nuts consumption compared to the control. From this dietary intervention trial, it can be concluded that almonds and pistachio mixture improved anti-oxidants and pro-oxidants status compared with those of the healthy volunteers.